New Expression of the Changing Stress Field in Low-Permeability Reservoir and its Application in Secondary Exploitation. Issue 4 (August 2015) - Du, Shuheng; Shi, Yongmin; Bu, Xiangqian; Jin, Wenqi; Mu, Guoquan
This study attempted to more accurately predict the latest three-dimensional stress field model between production and injection wells by integrating conclusion of mechanics measurement under in-situ conditions, data of pore pressure tests, logging, fine description regarding reservoirs and 3D modeling technology. Studies suggest that among the four major external factors which could result in the change of in-situ stress field such as temperature, confining pressure, pore pressure and fluid saturation, pore pressure played a major role. The latest model could be used to guide the optimization of the new 5 infilling wells fracturing design. The results show that the average daily oil production of a single well is 3.5 ton with moisture content of 24.5%. The conclusion will be used to improve the recovery during middle and later periods of low permeability reservoirs during secondary exploitation.